KEUNTUNGAN MENYIMPAN PADI HASIL PANEN - Sri Nuryanti; Mas Masyhuri (Agro Ekonomi, 2004)
Many decisions could be made by farmers after their paddy was getting mature and harvest time was coming. Some of them would sell their harvest directly to the ‘Tebasan’, and some another stored their harvest as dry paddy grain or rice and sold them one day if they thought price of paddy or rice is profitable.Farmers who sold their harvest directly have no probability of storage activity. Farmers who stored their harvest have two probabilities e.g. gain profit or loose at that time.Many farmers got loose after stored their harvest and sold as dry paddy grain or rice. Non financial incentive for farmers who stored their harvest.